The Malaysian intellectual: A brief historical overview of the discourse - Johnson, Deborah (Universiti Kebangsaan Malaysia, 2009)
This paper focuses on the discourse in Malaysia concerning intellectuals. It asserts that in concert with political and sociological changes, the ‘field of meanings’ associated with the concept of ‘the intellectual’ and the actual social location of intellectual actors have undergone considerable change during the twentieth century. This flags the challenge for historians who are telling today’s stories about the past in today’s terms, but who have to try to understand that past on its own terms. Further, it flags the challenge for social scientists to not merely appropriate the concepts of past scholars in tying to understand the present, but rather to also understand the context in which those ideas had relevance. Along the way, this paper gives glimpses of the circumstances, motivations and contributions of a number of leading Malaysian intellectual figures